Effects of durian sawdust as a partial replacement of fine aggregate in concrete - Che Deraman, Siti Noratikah; Abdul Rashid, Muhammad Afif Daniel; Saad, Siti Asmahani; Md.Husain, Nadiah; Masjuki, Siti Aliyyah (IOP Publishing Ltd, 2021)
Recently, many researches all over the world are focusing on ways of utilizing either industrial or agricultural wastes as a source of raw materials for the construction industry. The aim of this study is to determine the optimum proportion of durian saw dust as partial replacement for fine aggregate. These wastes utilization would not only be economical but may also help to create a sustainable and pollution free environment. Durian sawdust is one such fibrous waste-product from durian skin. In this paper, untreated durian sawdust has been partially replaced in the ratio of 0%, 5%, 10% and 15% by volume of fine aggregate in concrete. Fresh concrete tests like compacting factor test and slump test were undertaken along with hardened concrete tests like compressive strength test and UPV test. The result shows that durian sawdust of 5% partially replacement of fine aggregate can be used for structural and non-structural purposes.